Content Analysis of News on COVID-19 Rising during April 2023 in Bangkokpost.com - Thammasat Pitakpon; Daniel Susilo (Cita Konsultindo Research Center, 2023)
COVID-19 has been a great disaster for the world and entire society where it challenges not only mentality but also the lifestyle itself. Media is also part of people struggles in facing COVID-19. When a pandemic occurs, panic buying is the proof that people cannot stay calm when pandemic comes; that includes the panic within people in general. The role of media with Karen and Kevin’s media analysis helps us find how forming public opinion is important in order to perform panic control within the government as the death case raise again in April. Bangkok Post shows us this kind of capability despite the fact that the country itself is a developed country.